3 - Regional Economic Integration and the Governance Challenge in Africa: Missing Links in the African Peer Review Mechanism - Jiboku, Peace Akudo; Okeke-Uzodike, Ufo (Africa Development, 2021)
There exists a growing consensus among scholars and observers that critical issues on governance and development in Africa, which have remained unresolved, continue to pose obstacles to Africa’s economic integration efforts. Although the continent has witnessed different stages in the evolution of regional economic integration, and notwithstanding that regionalism has continued to occupy a central position in Africa’s development agenda, there is a missing link between the efforts of African states and regional organisations towards realising key regional integration objectives. This is especially because of two sets of factors: salient issues such as lack of good governance and democracy, poor leadership and domestic mismanagement; and continuing emphases on absolute sovereignty and the attendant issues around national interests versus regional interests. Thus, Africa has remained the least integrated and developed of the world’s major regions. This article examines the regional economic integration problematic in Africa from the angle of governance deficits in African countries. The article adopts a qualitative research methodology and is based on data obtained from literature, primary sources (interviews) and official documents/archival materials. Using a thematic discourse analysis and drawing insights from functionalism/neo-functionalism and neo-realism theories, the article assesses the effectiveness of the African Peer Review Mechanism (APRM) in interrogating issues on regionalism in Africa. It identifies missing links in the APR process in furthering the African Union/NEPAD integration and development objectives.